أثر تقلبات أسعار النفط على فعالية السياسة المالية كآلية لدعم النمو الاقتصادي - عماني, اسماعيل (جامعة الوادي - University of Eloued, 2018)
This study aims to analyze the effect of cyclical fluctuations in fiscal policy in response to the fluctuations in international oil prices on the economic growth of Algeria in the period from 1970 to 2014. To achieve this result, the GMM method was applied to the reaction function of the fiscal policy using annual data. The results conclude that Algeria's fiscal policy is cyclical and there is a moderate response to fluctuations in oil revenues caused by international price volatility. But the financial authorities are reversing these fluctuations on investment expenditures only. These results may explain the weak impact of fiscal policy instruments on economic growth in Algeria.
The impact of oil price fluctuations on the effectiveness of fiscal policy as a mechanism to support economic growth
مقال
Keywords: سياسة مالية, اسعار النفط, دورية. طريقة العزوم المعممة, الجزائر.